Concepts and concerns in remodeling swine facilities - P Murphy (Kansas Agricultural Experiment Station Research Reports, 1987)
Shall I remodel or burn it down? Determining an answer to this question requires careful consideration of construction costs and production goals. When considering a particular building - consider the following:; Swine Day, Manhattan, KS, November 19, 1987
Keywords: Swine day; 1987; Kansas Agricultural Experiment Station contribution; no. 88-125-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 528; Swine; Remodel; Swine facilities